(untitled) (Asian Journal of Medical and Biological Research, 2023)
One of the viral diseases affecting both domestic and wild animals in many countries around the world is foot and mouth disease (FMD). The livestock sector has been suffering significant financial losses for many years as a result of the disease. The present research work was focused on the isolation, documentation and serotyping of the Foot and Mouth Disease (FMD) virus from different locations. Reverse Transcription Polymerase Chain Reaction (RT-PCR) was used to detect the FMD virus (FMDV) serotype-O that is currently circulating in the BHK-21 cell line. All the tested samples were positive for FMDV and specific for serotype-O was 64.67-52.67% from tongue epithelium tissues and 30.67-16.67% from foot tissues respectively based on locations. In BHK-21 cell lines, the viruses caused cytopathic effects such as rounding, enlargement, intercellular bridge breakdown, and finally, death of cells, which shows the presence of the FMD virus under an inverted microscope. The BHK-21 cell culture fluid was found positive for FMDV in cell culture and also was positive based on CPE. Once more, the resulting inoculum was used to serotype the virus using RT-PCR. Based on the result of the RT-PCR method, the conclusion reached was that the serotype of the FMD virus was ‘Type O’. Asian J. Med. Biol. Res. 2023, 9 (2), 14-22